Monoclonal autoantibodies in Heymann nephritis. - Kimura, S (1986)
We have developed hybridoma cell lines, each of which secretes a monoclonal antibody (MoAb) to rat renal and hepatic tissue antigens, from Lewis rat with Heymann's nephritis. Three antibodies bind to the brush border of proximal tubular epithelium (BB), one in a fine net-like pattern (no. 3-11), another one in a coarse granular pattern (no. 1-8) and the third one in a typical pattern (no. 3-9). Three antibodies bind to glomerulus in characteristic patterns but not to BB. After repeated intravenous injections of MoAb (no. 3-11), granular mesangial deposits of rat IgG were observed and of MoAb (no. 1-8), fine granular deposition along capillary walls. These monoclonal autoantibodies should be of value in research on the mechanism of autoimmune membranous nephropathy.